Structure of rhythmic gymnastics trainings center in Brazil - Fernandes Antualpa, K.; Rodrigues Paes, R. (Science of Gymnastics Journal, 2013)
This study was elaborated with the purpose of knowing and describing the context of rhythmic gymnastics (RG) training centers (TC) in Brazil. This paper discusses the training centers, contextualizing the topic of this study, and configuring its scenario in Brazil. Qualitative research has been used, in order to meet the needs of the study. Data collection was done by non-participant observation, by means of a field journal, as well as by the description of the obtained data. Finally, data discussion was done, showing similarities and differences between the training centers assessed, always approaching the discussion of the physical structure of these places, and aiming, at the end of the discussion, to focus on the usefulness of these centers for the growth and development of the sport.